Effects of Radiographic Contrast Agents on Thrombin Formation and Activity - Fay, William P.; Parker, Andrew C. (Thrombosis and Haemostasis, 1998)
Clinical trials suggest that the risk of thrombosis during coronary angioplasty is lower with ionic contrast agents than with nonionic contrast agents. However, the molecular mechanisms underlying this effect are unknown. This study examined the effects of contrast agents on thrombin formation and its interaction with substrates, inhibitors, and ligands to define potential mechanisms by which contrast agents affect thrombus formation. Two ionic agents, diatrizoate and ioxaglate, and one nonionic agent, ioversol, were studied. Ionic agents inhibited factor X activation by the tissue factor-factor VIIa complex more potently than ioversol (53 ± 3.7, 43.0 ± 1.9, and 26.5 ± 2.4% inhibition by diatrizoate, ioxaglate, and ioversol, respectively, at concentrations of 5%). Ionic contrast agents were potent inhibitors of prothrombinase function, inhibiting thrombin formation by >75% at contrast concentrations of 0.6% (p <0.005). Ioversol inhibited prothrombinase to a significantly lesser extent than ionic agents. Clotting assays suggested that ioxaglate was the most potent inhibitor of thrombin generation in plasma despite having the least effect on fibrin polymerization. Contrast agents inhibited binding of thrombin to fibrin, with ionic agents producing a more potent effect than ioversol (p <0.02). However, contrast agents did not inhibit thrombin-mediated platelet activation, had only a minor effect on inhibition of thrombin by antithrombin III, and did not affect thrombin-hirudin interactions. In summary, these studies identify specific mechanisms by which radiographic contrast agents inhibit thrombin formation and function – i.e. inhibition of tissue factor-dependent factor Xa generation, inhibition of the prothrombinase complex, and inhibition of thrombin binding to fibrin. These findings may help to explain the reduced risk of thrombosis during coronary angioplasty associated with ionic contrast agents.